2002
DOI: 10.1097/00002508-200205000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Sex Hormone Suppression by Intrathecal Opioids: A Prospective Study

Abstract: Administration of intrathecal opioids may result in hypogonadotrophic hypogonadism. As part of the consent for therapy process, patients should be informed about this effect and its management. With long-term intrathecal opioid administration, the hypothalamic-pituitary-gonadal axis should be monitored. Where indicated, testosterone replacement should be undertaken to improve sexual function and prevent the potential metabolic effects of hypogonadism, in particular, osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
1
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(90 citation statements)
references
References 32 publications
7
78
1
4
Order By: Relevance
“…50 Chronic heroin abuse depresses testicular function through the inhibition of release of LH from the pituitary and the hormonal changes returned promptly to normal after withdrawal. 51 Whether erectile function could be restored needs further study. Hypersexuality episodes may be observed in men experiencing opiate withdrawal, with spontaneous erections and nocturnal ejaculation.…”
Section: ) Opioidsmentioning
confidence: 99%
“…50 Chronic heroin abuse depresses testicular function through the inhibition of release of LH from the pituitary and the hormonal changes returned promptly to normal after withdrawal. 51 Whether erectile function could be restored needs further study. Hypersexuality episodes may be observed in men experiencing opiate withdrawal, with spontaneous erections and nocturnal ejaculation.…”
Section: ) Opioidsmentioning
confidence: 99%
“…It has been confirmed that heroin abusers have serious sexual dysfunction, including decreased sexual drive, erectile dysfunction and delayed ejaculation [52][53][54][55][56], and that heroin-induced sexual potency reduction is associated with directing blood flow away from the genitals. Further, it direcly correlates with the deteriorated physical and psychological status and living environment of heroin users [57].…”
Section: Outcomementioning
confidence: 99%
“…Fait trĂšs intĂ©ressant, l'administration d'opioĂŻdes entraĂźne l'inhibition de l'axe hypothalamo-hypophysogonadique. Il en dĂ©coule une diminution des niveaux de testostĂ©rone [44]. Il faut donc toujours garder Ă  l'esprit de compenser cette baisse d'androgĂšnes lors d'une administration chronique d'opioĂŻdes afin de ne pas enclencher un cercle vicieux.…”
Section: Et Chez L'humain ?unclassified